New species of Philobryidae (Bivalvia: Pteriomorphia) from Patagonian and Antarctic waters - Urcola, Matías Ricardo; Zelaya, Diego Gabriel (Zoologischer Anzeiger)
Despite being one of the most diversified families of mollusks in sub-Antarctic and Antarctic waters, Philobryidae Bernard, 1897 still appears as a poorly studied family of bivalves. The aim of this study is to contribute to a better understanding of this family, by redescribing Philobrya wandelensis Lamy, 1906 and describing three new species from Patagonia and the adjacent Antarctic waters. Two new species here described closely resemble P. wandelensis, and in fact, at least one of them was previously reported in the literature under that name. The hinges of these species are compared with that of Bryophila setosa Carpenter, 1864, the type species of Philobrya J.G. Cooper, 1867, for which the ontogenetic variation is described for the first time. Furthermore, Hochstetteria Vélain, 1877 is removed from the synonymy of Philobrya, as regarded by several recent authors. The remaining new species described belongs to Verticipronus Hedley, 1904 (type species: Verticipronus mytilus Hedley 1904; lectotype here designated), a genus here reported for the first time in Patagonian waters. New arguments supporting the placement of Verticipronus in Philobryidae are provided. The new species here described presents transposition of hinge teeth. The frequency of this phenomenon in that species proved to be higher than that reported for any other bivalve. Fil: Urcola, Matías Ricardo. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina